Lithothamnion sp. Como Bioestimulante De Plantas - Ramos, Elmo Pereira (2024)
Lithothamnion sp. is a calcareous algae used in agriculture as a mineral fertilizer. However, studies indicate biostimulant effects in several agricultural crops, but progress is still needed in identifying the mechanisms. The present study consists of four chapters that address the biostimulant effects of the alga Lithothamnion sp. in plants. In the first chapter, the main applications of Lithothamnion sp. in agricultural crops were described in the form of a bibliographical review. In the second and third chapters, different sources of Lithothamnion sp. were evaluated. to identify the dose that results in better quality of seedlings and greater accumulation of nutrients for papaya ‘Aliança’ (Carica papaya L.). In the fourth chapter, the biostimulant effect of Lithothamnion sp. was evaluated. in interaction with indolebutyric acid (IBA) in the development of the root system, vegetative growth, gas exchange and seedling quality of two black pepper cultivars (Piper nigrum L.) ‘Bragantina’ and ‘Kottanadan Broto Branco’. Through the biobliographic review, it was possible to highlight the positive effects of Lithothamnion sp. in stimulating plant growth, fruit quality, productivity and gas exchange, highlighting the auxinic action and the induction of resistance to biotic and abiotic stress. The incorporation of Lithothamnion sp. in the substrate (Chapter 2) and foliar application via drenching (Chapter 3) promoted changes in the quality of seedlings and nutritional content in the “Aliança” papaya tree, mainly calcium, potassium, manganese and zinc. In general, it was noted that Lithothamnion sp. extracted from deposits in Espírito Santo have a greater biostimulant effect on papaya seedlings, compared to those extracted in the states of Maranhão and Bahia. The ideal dose varied between 5 and 6 g L-1 when applied foliarly and 4 Kg m-3 when incorporated into the substrate. In black pepper seedlings, it was noted that the effect of Lithothamnion sp. was independent of indolebutyric acid and cultivars. Lithothamnion sp. promoted shoot growth and root length, with a better response at a dose of 1,80 kg m-3 . However, increasing concentration inhibited adventitious rhizogenesis. The presence of IBA resulted in greater accumulation of biomass, root volume, shoot growth and water use efficiency, providing greater values in the development of seedlings. In the presence of IBA, higher values in seedling development were observed for the cultivar ‘Kottanadan Broto Branco’. In conclusion, it was evident (1) the biostimulating effect of Lithothamnion sp. in the seminal seedlings of the “Aliança” papaya tree and (2) the effectiveness of lower doses of the biostimulant for the clonal seedlings of the black pepper cv. ‘Bragantina’ and ‘Kottanadan Broto Branco’.